Synaptic transmission is dispensable for selecting the winner input but is crucial for the subsequent events of synapse elimination - Tzu-Huei Kao; Yuto Okuno; Kyoko Matsuyama; Takaki Watanabe; Naofumi Uesaka; Masanobu Kano (Proceedings of the National Academy of Sciences, 2025)
Synaptic transmission has long been thought to regulate neuronal wiring during postnatal development, but this assumption remains largely untested. Selective strengthening of a single “winner” climbing fiber (CF) afferent to each Purkinje cell (PC) and elimination of the other “loser” CF axons in the cerebellum has been a representative model of neural circuit refinement. Here, we examined the role of neurotransmission at CF-PC synapses in their postnatal development. We labeled a subset of CFs in neonatal mice with fluorescent markers and the tetanus toxin light chain to ablate neurotransmitter release from these CFs. Surprisingly, we found that such neurotransmitter release–deficient CFs were able to become the winners. However, synaptic transmission was crucial for the winning CF to extend its synaptic territory along the PC dendritic arbor and eliminate the loser CFs. These findings reveal how synaptic transmission governs multiple steps of synapse elimination but not the selection of the winner input that persists throughout life.